Autologous Parietal Peritoneum as a Biliary Interposition Conduit for Complex Post-Cholecystectomy Bile Duct Injuries: A Feasibility Study and Report of Two Cases - Elena Wandantyas; Anung Noto Nugroho (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Complex iatrogenic bile duct injuries (BDIs) are formidable surgical challenges, with Roux-en-Y hepaticojejunostomy (RYHJ) being the standard reconstruction. However, RYHJ permanently alters gastrointestinal physiology and is associated with significant long-term morbidity. This has prompted a search for physiology-preserving alternatives. We describe a novel technique using a tubularized autologous parietal peritoneal graft for biliary reconstruction. Case presentation: This report details the successful management of two patients with high-grade, post-cholecystectomy BDIs (Strasberg-Bismuth Type E1 and E3). Both patients presented with obstructive jaundice and controlled biliary fistulae. Definitive single-stage reconstruction was performed. A segment of parietal peritoneum was harvested, tubularized over a T-tube to create an interposition conduit, and anastomosed to bridge the biliary defect. The repair was reinforced with a pedicled omental flap. Both patients demonstrated complete resolution of jaundice and normalization of liver function tests, with radiological evidence of graft patency and no stricture at 12-month follow-up. Conclusion: This preliminary experience in two patients suggests that the use of a tubularized autologous parietal peritoneal graft is a surgically feasible technique for the reconstruction of complex BDIs. This approach offers a potential physiology-preserving alternative to traditional bilioenteric anastomosis. Its safety, efficacy, and long-term durability remain unknown and require rigorous evaluation in larger prospective studies.